Thermal, flammability, and antimicrobial properties of arrowroot (Maranta arundinacea) fiber reinforced arrowroot starch biopolymer composites for food packaging applications - Tarique, Jamal; Salit, Mohd Sapuan; Khalina, Abdan; Ilyas, R. A.; Zainudin, Edi Syams (Elsevier, 2022)
Using the solution casting method, a novel biodegradable thermoplastic arrowroot (Maranta arundinacea) starch (TPAS) films containing arrowroot fiber (AF) at different concentrations (0, 2, 4, 6, 8, and 10 wt%) were developed and characterized in terms of thermal, antibacterial activity, water vapor permeability (WVP), biodegradability, and light transmittance properties. The TPAS/AF-10 biocomposite film revealed a higher degradation temperature (313.02 °C) than other biocomposite films, indicating better thermal stability. Furthermore, increasing AF concentration led to a significant (p < 0.05) reduction in the linear burning rate and WVP of the biocomposite films from 248.9 to 115.2 mm/min and 8.18 × 10−10 ×g. s−1.m−1. Pa−1 to 5.20 × 10−10 ×g. s−1.m−1. Pa−1, respectively. The addition of fibers in the surface structure had a significant impact on remarkable drop in opacity (91.1 to 74.1%). In addition, the incorporation of AF and control film showed an insignificant effect against three pathogenic bacteria, including Staphylococcus aureus (ATCC 43300), Escherichia coli (ATCC 25922), and Bacillus subtilis (B29). The soil burial findings demonstrated that the weight loss of TPAS/AF biocomposite films was significantly higher than TPAS film. Overall, the reinforcement of arrowroot fiber with TPAS film improved the properties of biocomposites for environmentally friendly food packaging applications.